Efeito in vitro do ácido tânico sobre células planctônicas e biofilmes de Candida ssp. e seu mecanismo de ação - Moreira, Lara Elloyse Almeida (2024)
Fungal infections are an emerging public health problem, particularly in nosocomial settings and in immunosuppressed patients. Candida spp. is characterized as an important opportunistic genus that, over the years, presents more and more strains resistant to the antifungal treatments used. With increasing clinical resistance, a change in the epidemiology of Candida infections is observed, which highlights the need for new therapeutic strategies. In this context, products of natural origin stand out for presenting reports in the literature about their in vitro antifungal activity, in which tannins are an important class of emphasis. In this context, tannic acid is a hydrolyzable tannin that has several biological properties already demonstrated in vitro, such as antioxidant and anticancer, as well as antimicrobial against viruses, parasites and bacteria. However, there are few reports in the literature about its antifungal properties against Candida spp. Therefore, the present study aimed to evaluate the in vitro antifungal activity of tannic acid, isolated and associated with antifungals commonly used in therapy, as well as evaluating its cytotoxicity, its antibiofilm property and elucidating its mechanism of action against Candida. spp. sensitive and resistant to fluconazole. The broth microdilution technique was used to determine the Minimum Inhibitory Concentration (MIC) and the checkerboard technique was used to determine the pharmacological interaction between tannic acid and antifungals. The evaluation of cytotoxicity was evaluated in L929 murine fibroblast cells and its hemolytic effect on mouse red blood cells. Its mechanism of action was evaluated by flow cytometry assays and its antibiofilm effect was evaluated in 96-well plates. Tannic acid showed MICs ranging from 0.06 to 0.5 μg/ml. Pharmacological interaction tests demonstrated that 100% of interactions were indifferent in the combination of tannic acid + amphotericin B; 93.75% of the interactions were indifferent and one strain showed an antagonistic interaction in the combination of tannic acid + itraconazole and the combination of tannic acid + fluconazole showed 75% of indifferent interactions, 12.5% synergistic and 12.5% additive. Tannic acid did not present cytotoxic and hemolytic effects at the concentrations at which it exerts its antifungal activity. Furthermore, it is indicated that its mechanism of action is exerted through pro-oxidant activity, with the production of reactive oxygen species in fungal cells, which generate oxidative stress, resulting in the induction of signals that mediate apoptosis. Its antibiofilm activity occurs in higher concentrations, inhibiting around 50% of the biofilm at concentrations of 128x MIC. Therefore, tannic acid has potential antifungal activity against strains sensitive and resistant to fluconazole at safe concentrations, both in planktonic cells and in biofilm. However, more studies are needed to promote such applications in vivo.